A generalised force equivalence-based modelling method for a dry wind-tunnel flutter test system. (April 2021) - Zhang, Z.; Gao, B.; Wang, J.; Xu, D.; Chen, G.; Yao, W.
ABSTRACT: Dry wind-tunnel (DWT) flutter test systems model the unsteady distributed aerodynamic force using various electromagnetic exciters. They can be used to test the aeroelastic and aeroservoelastic stability of smart aircraft or high-speed flight vehicles. A new parameterised modelling method at the full system level based on the generalised force equivalence for DWT flutter systems is proposed herein. The full system model includes the structural dynamic model, electromechanical coupling model and fast aerodynamic computation model. An optimisation search method is applied to determine the best locations for measurement and excitation by introducing Fisher's information matrix. The feasibility and accuracy of the proposed system-level numerical DWT modelling method have been validated for a plate aeroelastic model with four exciters/transducers. The effects of key parameters including the number of exciters, the control time delay, the noise interference and the electrical parameters of the electromagnetic exciter model have also been investigated. The numerical and experimental results indicate that the proposed modelling method achieves good accuracy (with deviations of less than 1.5% from simulations and 4.5% from experimental test results for the flutter speed) and robust performance even in uncertain environments with a 10% noise level.